Analysis of Product and Temperature of Biogas Combustion in Various Air Biogas Equivalence Ratio and Methane Content - Arini Wresta; Aep Saepudin (Indonesian Journal of Chemistry, 2018)
Biogas resulted from anaerobic digestion of organic compounds have various methane content depend on the type of the degraded material. The methane content of biogas is range between 40–80% that influence the heating value and combustion characteristic of that biogas. The higher methane content can be obtained through upgrading biogas by removing CO2 and other trace components like H2S, NH3, and water vapor. This research was a simulation of product composition and temperature of biogas combustion in various methane content and air biogas equivalence ratio. Biogas combustion was done in combustion chamber at constant pressure of 1 atm. Biogas and air enter into combustion chamber at temperature approximately of 30 °C as the common ambient temperature in Indonesia. The input air was designed higher than stoichiometric need in order to reach complete combustion. Combustion reaction between methane and O2 then carried out in the combustion chamber to produce CO2 and H2O. The product gases consisting of CO2, H2O, N2, and excess O2, bring heat from combustion reaction and exit from combustion chamber at the higher temperature. The analysis was done for methane content range between 20 and 100% with air biogas equivalence ratio from 1 until 3. The simulation result showed that for V m3 biogas, the combustion gases could reach 0.12271 until 1.26798V gmol with temperature above 700 °C until above 1900 °C. More than 50% component in the combustion gases is N2 as inert material from input air to combustion chamber.